Pathogenicity of Beauveria bassiana (Deuteromycota: Hyphomycetes) to the red cashew beetle Crimissa cruralis (Coleoptera: Chrysomelidae: Galerucinae: Blepharida-group) in laboratory conditions - Araújo-de-Souza, Suyanne; De Sousa-Maciel, Gabriela Priscila; Dias-Pini, Nívia Da Silva; Gonçalves-Barbosa, Marianne; Martins-Duarte, Poliana; Pastori, Patrik Luiz (Revista Colombiana de Entomología, 2019)
The increased pest actions of the red cashew beetle Crimissa cruralis (Coleoptera: Chrysomelidae in Brazilian populations of cashew Anacardium occidentale (Anarcardiaceae) is a cause for concern. The entomopathogenic fungus, Beauveria bassiana, was evaluated as a biocontrol of larvae. The percent mortalities of second and third instar larvae produced by in vivo application of a commercial formulation containing the fungal spores were evaluated. Treatment of larvae at concentrations of 1.2 x 106, 2.5 x 106, 3.7 x 107 e 5.0 x 107 conidia/mL resulted in 49, 56, 66 and 72 % mortality within eight days, respectively. Based on the finding, it is recommended that the B. bassiana formulation should be employed at the lowest concentrations (1.2 x 106 and 2.5 x 106 conidia/mL) with repeat application to avoid possible inactivation of the fungus by abiotic environmental factors. Cost-benefit assessments of the use of this biological agent will be important for determining the economic feasibility of its application in the field.